The effect of washing for the shelf-life parameters of spinach (Spinacia oleracea L.) - Pócsik-Sáfrány, Krisztina; Ansaroudi, Rana Shahriyari; Zabiák, Andrea; Mihály, Kata; Csótó, András; Sándor, Erzsébet (Acta Agraria Debreceniensis, 2024)
Spinach is a very popular green leafy vegetable because of its versatile usage and beneficial for the health. However, spinach may contain several pathogen bacteria: Escherichia coli, Klebsiella spp., Salmonella spp., Enterobacter spp., Citrobacter spp., Shigella spp. and Listeria monocytogenes, which can cause several serious health problems. This study investigates the effects of washing with citric acid for the shelf-life parameters of spinach in comparison to the effect of washing with water and control. Washing of spinach with 0.5% citric acid solution decreased the elasticity of the spinach leaves, as well as the chlorophyll content. On the other hand, the total plate count, as well as the yeast and mold count could be decreased with this treatment, but difference was not detectable at the forth storage day. The fecal indicator E. coli did not change, indicating washing was not effective in this case. Further optimisation of treatment and storage conditions may decrease microbial risk of fresh spinach consumption without decreasing its sensory quality.